STUDI PENGGUNAAN ANTIHIPERTENSI ORAL PADA PASIEN HIPERTENSI RAWAT JALAN DI PUSKESMAS NGESREP PERIODE 2025 - Silvianasari, Firly Nur (Jurnal Penelitian Farmasi Dan Herbal, 2026)
Hypertension is a chronic disease with a high prevalence and a significant contribution to morbidity and mortality in Indonesia. The appropriate use of antihypertensive drugs plays a crucial role in achieving optimal blood pressure control. This study aims to describe the pattern of oral antihypertensive use and evaluate its effectiveness based on changes in blood pressure before and after treatment among outpatient hypertension patients at Ngesrep Primary Health Center during the period of January–April 2025. This research employed an observational design with a retrospective descriptive approach through the review of medical records of hypertensive patients who met the inclusion criteria. A total of 30 medical records were obtained using purposive sampling. Data were analyzed using the Kolmogorov-Smirnov normality test followed by the Paired T-Test to assess differences in systolic and diastolic blood pressure before and after therapy. The results showed that amlodipine, particularly the 10 mg dosage, was the most frequently used antihypertensive. Statistical analysis demonstrated a significant reduction in both systolic and diastolic blood pressure after treatment (p < 0.05), indicating that the antihypertensive regimen administered was effective. In conclusion, oral antihypertensive therapy in this setting showed a positive effect in lowering blood pressure among outpatient hypertension patients